Time-Resolved Fluorescence Resonance Energy Transfer Assay for Discovery of Small-Molecule Inhibitors of Methyl-CpG Binding Domain Protein 2. (August 2014) - Wyhs, Nicolas; Walker, David; Giovinazzo, Hugh; Yegnasubramanian, Srinivasan; Nelson, William G.
Methylated DNA binding proteins such as Methyl-CpG Binding Domain Protein 2 (MBD2) can transduce DNA methylation alterations into a repressive signal by recruiting transcriptional co-repressor complexes. Interfering with MBD2 could lead to reactivation of tumor suppressor genes and therefore represents an attractive strategy for epigenetic therapy. We developed and compared fluorescence polarization (FP) and time-resolved fluorescence resonance energy transfer (TR-FRET)–based high-throughput screening (HTS) assays to identify small-molecule inhibitors of the interaction between the methyl binding domain of MBD2 (MBD2-MBD) and methylated DNA. Although both assays performed well in 96-well format, the TR-FRET assay (Z′ factor = 0.58) emerged as a superior screening strategy compared with FP (Z′ factor = 0.08) when evaluated in an HTS 384-well plate format. Using TR-FRET, we screened the Sigma LOPAC library for MBD2-MBD inhibitors and identified four compounds that also validated in a dose-response series. This included two known DNA intercalators (mitoxantrone and idarubicin) among two other inhibitory compounds (NF449 and aurintricarboxylic acid). All four compounds also inhibited the binding of SP-1, a transcription factor with a GC-rich binding sequence, to a methylated oligonucleotide, demonstrating that the activity was nonspecific. Our results provide proof of principle for using TR-FRET–based HTS to identify small-molecule inhibitors of MBD2 and other DNA-protein interactions.